2007
DOI: 10.1007/bf03393042
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-Stimulus Pairing and Subsequent Mand Acquisition of Children with Various Levels of Verbal Repertoires

Abstract: Effects of a stimulus-stimulus pairing procedure on the subsequent acquisition of mand operants were investigated. An attempt was made to shape novel sounds that emerged through the pairing procedure into a mand. Six children, aged two to five years, with moderate to severe language and communication delays, participated. Two conditions were used following the pairing condition: postpairing and direct reinforcement. The emergence of mands was compared across these conditions. An additional analysis was made of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 13 publications
1
36
0
1
Order By: Relevance
“…Within-session data are also frequently presented when responding occurs within a single, prolonged acquisition session (e.g., Arntzen & Almas, 2002;Rodgers & Iwata, 1991;Yoon & Feliciano, 2007). Yet, the demonstration of within-session analyses seems to be more thorough in the assessment and treatment of problem behavior than in the study of the acquisition of appropriate behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within-session data are also frequently presented when responding occurs within a single, prolonged acquisition session (e.g., Arntzen & Almas, 2002;Rodgers & Iwata, 1991;Yoon & Feliciano, 2007). Yet, the demonstration of within-session analyses seems to be more thorough in the assessment and treatment of problem behavior than in the study of the acquisition of appropriate behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Within-session analyses have been shown to aid in the evaluation of skill endurance (Martens et al, 1997) and the representation of differential patterns of newly acquired behavior (Hanley et al, 2001). Within-session data are also frequently presented when responding occurs within a single, prolonged acquisition session (e.g., Arntzen & Almas, 2002;Rodgers & Iwata, 1991;Yoon & Feliciano, 2007). Yet, the demonstration of within-session analyses seems to be more thorough in the assessment and treatment of problem behavior than in the study of the acquisition of appropriate behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated effects of SSP on the vocalizations of typically developing children (Smith, Michael, & Sundberg, ), children with language delays (Sundberg et al, ; Yoon & Bennett, ), and children with ASD (e.g., Esch, Carr, & Grow, ). However, several other studies with participants with ASD have reported mixed outcomes (Miguel, Carr, & Michael, ; Rader et al, ; Yoon & Feliciano, ) or null effects (Carroll & Klatt, ; Esch, Carr, & Michael, ; Normand & Knoll, ; Stock, Schulze, & Mirenda, ). Collectively, the literature suggests that SSP does not reliably affect vocalizations of children with ASD, perhaps because speech sounds are not reliably established as conditioned reinforcers for children with ASD (Petursdottir, Carp, Matthies, & Esch, ).…”
mentioning
confidence: 99%
“…A number of studies have reported positive effects on the vocalizations of children with and without ASD diagnoses (Carroll and Klatt 2008;Esch et al 2009;Lepper et al 2013;Miguel et al 2002;Miliotis et al 2012;Rader et al 2014;Sundberg et al 1996;Smith et al 1996;Stock et al 2008;Yoon and Bennett 2000;Yoon and Feliciano 2007). Some of these studies, however, have also reported negative results for one or more participants diagnosed with ASD or other disabilities (Carroll and Klatt 2008;Miguel et al 2002;Rader et al 2014;Stock et al 2008;Yoon and Feliciano 2007), and two studies with a total of four participants with ASD have completely failed to find an effect (Esch, Carr, and Michael 2005;Normand and Knoll 2006). Overall, in 13 published studies (see Table 1), stimulus-stimulus pairing has produced an effect on the vocalizations of 27 of 39 participants (69 %), including 16 out of 25 (64 %) participants with ASD diagnoses.…”
Section: Pairing Speech Sounds With Reinforcersmentioning
confidence: 99%
“…In addition, the clinical utility of inducing speech sounds through these procedures needs further investigation. To date, only a few studies have included demonstrations that the newly induced speech sounds can be Bcaught^and strengthened further via direct reinforcement (Esch et al 2009;Lepper and Petursdottir under review) or brought under stimulus control as functional vocalizations (Carroll and Klatt 2008;Yoon and Feliciano 2007).…”
Section: Future Directionsmentioning
confidence: 99%